5’isomiR-183-5p|+2 elicits tumor suppressor activity in a negative feedback loop with E2F1 - Li, Xiaoya; Michels, Birgitta Elisabeth; Tosun, Oyku Ece; Jung, Janine; Kappes, Jolane; Ibing, Susanne; Nataraj, Nishanth Belugali; Sahay, Shashwat; Schneider, Martin; Wörner, Angelika; Becki, Corinna; Ishaque, Naveed; et al. (Journal of experimental & clinical cancer research, 2022)
MicroRNAs (miRNAs) and isomiRs play important roles in tumorigenesis as essential regulators of gene expression. 5’isomiRs exhibit a shifted seed sequence compared to the canonical miRNA, resulting in different target spectra and thereby extending the phenotypic impact of the respective common pre-miRNA. However, for most miRNAs, expression and function of 5’isomiRs have not been studied in detail yet. Therefore, this study aims to investigate the functions of miRNAs and their 5’isomiRs.
Gesehen am 07.07.2022